Kampanye Sosial tentang Kepedulian terhadap Lansia - Sukina Sukina; Aditya Rahman Yani; Alfian Candra Ayuswantana (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The growing number of elderly in Indonesia demands more attention from families and communities towards their welfare. The many cases of elderly neglect show a lack of empathy and education regarding the role of families and communities in caring for the elderly. This study designed a social campaign entitled "Senja Kasih" which utilizes Instagram social media as a medium for delivering messages to the public. This campaign uses an emotional appeal approach to arouse audience emotions and empathy towards elderly issues. The research method used is mixed methods through interviews, observations, questionnaires, and literature studies. The design results include a campaign logo, visual concepts to increase the effectiveness of message delivery. This campaign collaborates with the Panti Lansia Yayasan Buddhayana Panditarama as a stakeholder. It is hoped that the "Senja Kasih" campaign can increase public awareness, build empathy, and encourage participation in supporting and caring for the elderly.